Serum Hepcidin-25 and Risk of Mortality in Patients on Peritoneal Dialysis - Zhong, Zhong; Luo, Dan; Luo, Ning; Li, Bin; Fu, Dongying; Fan, Li; Li, Zhijian; Chen, Wei; Mao, Haiping (Frontiers in Medicine, 2021)
Background: Increased serum hepcidin-25 level is associated with excess mortality in hemodialysis patients. However, there is a dearth of published information about its predictive effect for survival in patients on peritoneal dialysis (PD). The purpose of this study is to evaluate the association of serum hepcidin-25 with the risk of mortality in PD patients. Methods: Serum hepcidin-25 level was measured using an enzyme-linked immunosorbent assay in a prospective cohort study of PD patients with stored serum samples at baseline. Multivariate linear regression model was used to determine clinical characteristics associated with serum hepcidin-25 concentration. We evaluated the relationship between serum hepcidin-25 and all-cause mortality using a Cox proportional hazards model and the relationship between hepcidin-25 and cardiovascular (CV) and infection-related deaths using competing-risks regression models. Results: In total, 513 PD patients were included in this study. The median serum hepcidin-25 level was 40.9 (17.9–85.9) ng/mL. Body mass index and serum ferritin were positively correlated with serum hepcidin-25 levels. During a median follow-up period of 64.1 months, 122 (24%) patients died, including 61 (50%) CV deaths and 32 (26%) infection-related deaths. In multivariable analysis, patients with the highest tertile of serum hepcidin-25 had a greater risk of all-cause [adjusted hazard ratio (aHR) 1.85, 95% confidence interval (95%CI), 1.14 to 3.00, P = 0.013] and infection-related mortality (adjusted subdistribution hazard ratio [aSHR], 2.61; 95%CI, 1.01 to 6.76, P = 0.049) when compared with those in the second tertile. However, no significant relationship was observed between serum hepcidin-25 and CV mortality. Conclusions: Higher baseline serum hepcidin-25 level was associated with increased risk for all-cause and infection-related mortality in PD patients.